Effects of using a document holder when typing on head excursion and neck muscle activity among computer users with and without neck pain - Subramaniam, Ambusam; Davinder Kaur, Ajit Singh (Taylor & Francis, 2019)
Purpose. The aim of this study was to examine the effects of using a document holder while typing on head excursion and neck muscle activity among computer users with and without neck pain. Method. An experimental study including 52 individuals with (n = 26) and without (n = 26) neck pain was conducted. Head excursion and neck muscle activity were measured using an accelerometer and surface electromyography, respectively. Two-way analysis of variance was conducted to examine the effects of using a document holder between computer users with and without neck pain. Results. The results demonstrated a decrease in head excursion (p <0.001) and muscle activity of both the right and left upper trapezius and the left lower trapezius and right anterior deltoid (p <0.05) with the use of a document holder. Computer users with neck pain had significantly (p <0.001) higher right lower trapezius muscle activity compared to the group without neck pain. Conclusion. The results of the study supported the use of a document holder to assist in decreasing head excursion and neck muscle activity. The use of a document holder while typing may be beneficial in preventing repetitive strain injuries among computer users.